Yummy in my tummy healthy eating habits for babies - Castelino, Lianna; Howick, Andrea; Liandrea Company production; Cambridge Educational (Firm). (Lawrenceville, NJ : Cambridge Education, 2008)
Identifies the best diet choices for growing babies and the best ways to get them started on solid foods. Includes menu planning, pointers, recipes and step-by-step cooking.
There are five chapter or topic includes in the video which are : yummy eating habits, yummy first foods, yummy food groups, yummy questions and bonus recipes.
DVD format.
Keywords: Infants -- Nutrition; Baby foods